2015
DOI: 10.1103/physrevlett.114.080602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Thermodynamics: A Nonequilibrium Green’s Function Approach

Abstract: We establish the foundations of a nonequilibrium theory of quantum thermodynamics for noninteracting open quantum systems strongly coupled to their reservoirs within the framework of the nonequilibrium Green's functions. The energy of the system and its coupling to the reservoirs are controlled by a slow external time-dependent force treated to first order beyond the quasistatic limit. We derive the four basic laws of thermodynamics and characterize reversible transformations. Stochastic thermodynamics is reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
236
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(244 citation statements)
references
References 48 publications
7
236
1
Order By: Relevance
“…We provide in Section 3.2 some numerical calculations of the entropy production rate for a model system of a single electron resonance coupled to two Fermi reservoirs. A comparison to earlier results [11] is also given. In Section 4, we consider the NE entropy production in the entire system obtained from the Gibbs-von Neumann expression based on the NE density matrix.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…We provide in Section 3.2 some numerical calculations of the entropy production rate for a model system of a single electron resonance coupled to two Fermi reservoirs. A comparison to earlier results [11] is also given. In Section 4, we consider the NE entropy production in the entire system obtained from the Gibbs-von Neumann expression based on the NE density matrix.…”
Section: Introductionmentioning
confidence: 79%
“…One can study the NE thermodynamical properties and the entropy production in such systems when an external driving force is applied to the central region. The time dependence of the external force can be arbitrary or periodic [10,11,13,15]. The long-time limit behaviour of the NE thermodynamics also presents very interesting properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the same standpoint, thermal transport studies were conceived and came to be conclusive in the upcoming years [2]. Subsequently, several theoretical studies demonstrated the possibility to conduct both thermal and charge through tunneling junctions [26][27][28][29][30][31][32][33][34], both in presence and absence of lattice vibrations, although there is no generic framework that successfully is capable of describing the thermodynamic properties of nano junctions [8,14,35].…”
Section: Introductionmentioning
confidence: 99%
“…Several realizations of tunneling junctions comprising noble metal electrodes and polymers that absorb, emit, and transmit thermal have been reported [4,6]. The interest is, moreover, driven from the perspective of information science and technology with respect to entropy production rate [3,7] and the meaning of the thermodynamics in low dimensional systems [3,8,9]. This was motivated by the discovery of conducting polymers and solitonic electronic transport mechanisms discovered by Shirakawa, see [10] and references therein.…”
Section: Introductionmentioning
confidence: 99%